2020
DOI: 10.22430/22565337.1493
|View full text |Cite
|
Sign up to set email alerts
|

Representación del conocimiento de un proceso de co-creación de material educativo

Abstract: En esta investigación, el uso de la co-creación busca apoyar la generación de material educativo por parte de estudiantes con altas capacidades, gracias a la participación de profesores y padres de los estudiantes. Durante este proceso, las características de los estudiantes como la personalidad, los gustos, las necesidades y habilidades deben ser consideradas y consolidadas, para que el material educativo co-creado sea de interés para ellos. La creación de material educativo para estudiantes tiende a aislar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(29 reference statements)
1
1
0
1
Order By: Relevance
“…This study identified that the academic productivity of research seedbeds is intensely measured through the number of executed projects and published research documents, a finding that aligns with the observations of Flores et al (2019) and Meneses-Ortegón et al (2020). This quantitative approach highlights the importance of tangible outputs as key indicators of success.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study identified that the academic productivity of research seedbeds is intensely measured through the number of executed projects and published research documents, a finding that aligns with the observations of Flores et al (2019) and Meneses-Ortegón et al (2020). This quantitative approach highlights the importance of tangible outputs as key indicators of success.…”
Section: Discussionsupporting
confidence: 81%
“…The fifth construct, human resource development, represents the final product developed by students in the research group. This construct should be measured by the quantity of projects executed by students, as well as those currently underway (Garnica Estrada & Franco Calderón, 2020;Meneses-Ortegón et al, 2020). Additionally, the quantity of undergraduate theses and dissertations developed within the group's activities should be considered.…”
Section: Figure 2 Proposed Model For Evaluating Academic Productivity...mentioning
confidence: 99%
“…La mayoría de las aplicaciones de GC se enfocan a la extracción de asociaciones de entidades, como is-a y part-of (Seo et al, 2020;. En contraste, otros estudios consideran como base las diferencias del dominio de los estudiantes para representar, en un GC, las relaciones de prerrequisitos entre los puntos de conocimiento y la recomendación de ejercicios (Lv et al, 2018;Meneses et al, 2020); sin embargo, ellos solo proponen un método que examina los nodos del GC basados en el comportamiento de datos de un estudiante, colectados mediante un sistema de evaluación, pero no utilizan la evidencia proporcionada por el estudiante sobre el dominio de un AD para evitar la exhaustividad en la evaluación. Oramas et al (2017) y Qiao y Hu (2020) propusieron un método que enriquece la descripción de los nodos en un GC con información semántica.…”
Section: Revisión De La Literaturaunclassified